The effectiveness of a training program based on international standards of instructional technology in improving teaching practices and professional leadership skills among Arabic language teachers at the secondary level - Al-Enzi, Ahmad Abdullah (Journal of Educational and Psychological Sciences, 2021)
The current study aimed to identify the effectiveness of a training program based on international standards of instructional technology in improving teaching practices and professional leadership skills of Arabic language teachers at the secondary level in the State of Kuwait, and to achieve the study objectives, the semi-experimental approach based on one group was used with pre-post measurement. Of (30) teachers of the Arabic language at the secondary stage in the Hawalli Educational Zone in the State of Kuwait, and a note card for teaching practices and a measure of professional leadership skills were prepared, and their validity and reliability were confirmed.The results showed a statistically significant difference at the level of significance (α ≤ 0.05) between the average scores of the pre and post application of the observation card related to the teaching practices of teachers attributed to the benefit of the training program, and the program has achieved effectiveness in improving the teaching practices of teachers amounting to (0.95) according to ETA. A statistically significant difference was found at the level of significance (α ≤ 0.05) between the average scores of pre and post application in the professional leadership skills scale for teachers attributed to the benefit of the training program. The program also achieved effectiveness in improving teachers' professional leadership skills, reaching (0.94), according to the ETA factor.The study recommended the adoption of the training program used by the study, as it was based on international standards for educational technology, working to spread it and circulating it within the training programs for Arabic language teachers, and paying attention to holding training courses for teachers during service to familiarize them with international standards for educational technology.
Keywords: Training program; Educational Technology; Teaching Practices; Professional Leadership